1983
DOI: 10.2307/2403139
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Time, Chill Days and Prediction of Budburst in Picea sitchensis

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 132.174.254.159 on Wed, SUMMARY(1) The dates of budhurst of lateral shoots on 2to 10-year old trees of Picea sitchensis were recorded on fourteen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
419
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(450 citation statements)
references
References 22 publications
15
419
0
Order By: Relevance
“…The Spring-Warming model (Cannell & Smith, 1983), SeqSar and Par1Sar models (Chuine et al, 1999) were used in the present analysis because they have been shown to be the most effective models among the different ones proposed in the literature. The Spring-Warming model assumes that budburst occurs when a critical sum of degree-days (more generally named forcing units, F *) above a certain threshold (Tb), cumulated from a fixed date (t " ) is attained ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The Spring-Warming model (Cannell & Smith, 1983), SeqSar and Par1Sar models (Chuine et al, 1999) were used in the present analysis because they have been shown to be the most effective models among the different ones proposed in the literature. The Spring-Warming model assumes that budburst occurs when a critical sum of degree-days (more generally named forcing units, F *) above a certain threshold (Tb), cumulated from a fixed date (t " ) is attained ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For each site, three trees were monitored weekly and scored according to Tenow et al (2001) phenophases for birch buds/leaf development. However, because Tenow et al (2001) phenophases could not be accurately judged from the landscape scale photographs; six clearly identifiable phenophases were assigned (see Supplementary Table), and matched to those described by Tenow. Thermal requirement for full foliage cover was calculated according to Cannell and Smith (1983) for each year. Base temperatures of 0, 0.5, 1, 1.5 and 2°C were considered; with accumulations beginning 1st March (no instances of positive temperatures occurred prior to this date).…”
Section: Methodological Analysismentioning
confidence: 99%
“…The effective temperature is a function of air or leaf temperature and differs between models. The integrated effective temperature in each development stage is referred to as the thermal time of that development stage (Cannell and Smith, 1983;McMaster and Wilhelm, 1997); there may also be an additional photoperiod length dependence. The thermal time in each development stage is typically set by the user and can be calibrated to simulate different varietal properties.…”
Section: Motivationmentioning
confidence: 99%